Preconditioning by Hydrogen Peroxide Enhances Multiple Properties of Human Decidua Basalis Mesenchymal Stem/Multipotent Stromal Cells - T. Khatlani; D. Algudiri; R. Alenzi; A. M. Al Subayyil; F. M. Abomaray; E. Bahattab; A. S. AlAskar; B. Kalionis; M. F. El-Muzaini; M. H. Abumaree (Stem Cells International)
Stem cell-based therapies rely on stem cell ability to repair in an oxidative stress environment. Preconditioning of mesenchymal stem cells (MSCs) to a stress environment has beneficial effects on their ability to repair injured tissues. We previously reported that MSCs from the decidua basalis (DBMSCs) of human placenta have many important cellular functions that make them potentially useful for cell-based therapies. Here, we studied the effect of DBMSC preconditioning to a stress environment. DBMSCs were exposed to various concentrations of hydrogen peroxide (H2O2), and their functions were then assessed. DBMSC expression of immune molecules after preconditioning was also determined. DBMSC preconditioning with H2O2 enhanced their proliferation, colonogenicity, adhesion, and migration. In addition, DBMSCs regardless of H2O2 treatment displayed antiangiogenic activity. H2O2 preconditioning also increased DBMSC expression of genes that promote cellular functions and decreased the expression of genes, which have opposite effect on their functions. Preconditioning also reduced DBMSC expression of IL-1β, but had no effects on the expression of other immune molecules that promote proliferation, adhesion, and migration. These data show that DBMSCs resist a toxic environment, which adds to their potential as a candidate stem cell type for treating various diseases in hostile environments.